Homebuyers superstitious belief: feng shui and housing property - Hassan, Mohammad Mujaheed; Ahmad, Nobaya; Hashim, Ahmad Hariza (Human Resource Management Academic Research Society, 2021)
This article aims to explore the superstitious belief in selecting housing property in Malaysia. Various types of superstitions have been passed down through the ages and remain until today. Based on the instrumental perspective of Feng Shui, prospective buyers instill a belief that success and wealth are influenced by Feng Shui arrangements. Whether Feng Shui is associated with property purchase is a question. Overall, these principles are instilled in the minds of an intuitive Feng Shui believer and implemented in a property purchase. Furthermore, Malaysians are involved in various taboos, folklores, and taboos besides Feng Shui when deciding on property purchase. While some investors make a vow by it as to not make any proceedings before the consultation with their expert, other investors perceive the myths as merely nonsense and old wives’ tales. This study are expected to provide guidance to property stakeholders (developers, real estate agencies, architects, local authorities) in their future development projects. For homebuyers, this study serves as a property Feng Shui checklist for home selection and investment.